Integration of social exchange theory: spiritual leadership on millennial organizational performance - Maksum, Ikhsan; Khan, Ryan Basith Fasih (Journal of Management and Digital Business, 2024)
For organizations whose members are predominantly Muslim, the appropriate leaders are leaders who have Islamic values ​​or what is usually called spiritual leadership. Based on the spiritual leadership approach, encouraging employees to participate in ta'awun behavior enhances human resources efficiency within a business organization. Researchers have studied many leadership models, but only a few have explored spiritual leadership models and OCBI and OCBO on human resource performance. The study aims to contribute to the growth of research into spiritual leadership models, OCBI, and OCBO behavior about HR performance. This study investigates the mediating role of ta'awun behavior in the relationship between spiritual leadership and HR performance. This study emphasizes 190 employees from PT Arkatama Solusindo and PT Digi Partner Studio and a quantitative research paradigm using the Partial Least Squares (PLS) analysis tool. According to this research, the spiritual leadership model is the most effective factor for improving human resource performance. Its influence can be effectively reduced by OCBI and OCBO behavior. OCBI behavior serves as a mediator for the impact of spiritual leadership on HR performance. Meanwhile, the mediating variable OCBO does not have a mediating role.